Direct Determination of Levoglucosan at the Picogram per Milliliter Level in Antarctic Ice by High-Performance Liquid Chromatography/Electrospray Ionization Triple Quadrupole Mass Spectrometry - GAMBARO, Andrea; ZANGRANDO R.; GABRIELLI P.; BARBANTE, Carlo; CESCON, Paolo (Analytical Chemistry, 2008)
A method for the direct determination of levoglucosan at the pg mL-1 level in less than 1 mL of Antarctic ice has been developed. Chemical analysis is performed by high-performance liquid chromatography with triple quadrupole tandem mass spectrometric detection. Levoglucosan, a specific molecular marker for biomass burning, is identified by negative ion electrospray mass spectrometry using m/z 161/113, 161/101, 161/85, 161/71 as monitoring ion transitions. Contamination problems were carefully taken into account by adopting ultraclean procedures during sampling and sample pre- treatment phases. The limit of detection is 3 pg mL-1 (0.3 pg absolute amount injected); the repeatability ranges between 20% and 50% at a concentration of 20 pg mL-1 and 9 pg mL-1 respectively. This methodology allowed the direct determination of levoglucosan in a 1 mL sample of Antarctic ice with concentration ranges between 4 pg mL-1 and 30 pg mL-1. To our knowledge these are the first levoglucosan concentrations reported for Antarctic ice.